Improving on whole-brain radiotherapy in patients with large brain metastases: A planning study to support the AROMA clinical trial. (May 2022) - Chen, Jiarong; Sinclair, Georges; Rozati, Hamoun; Hill, Laurence; Pakzad-Shahabi, Lillie; Wang, James; Calvez, Kerlann Le; Paddick, Ian; Williams, Matt
Graphical abstract: Highlights: Radiotherapy for 1 to 10 brain metastases and at least one lesion larger than 15 cm 3 . Comparison of VMAT plans with WBRT and HS-WBRT. Development of a novel dose-escalated internal PTV model with VMAT. Performance of dose distributions within the tumours and OARs. Abstract: Purpose: To develop a novel dose-escalated volumetric modulated arc therapy (VMAT) strategy for patients with single or multiple large brain metastases which can deliver a higher dose to individual lesions for better local control (LC), and to compare dosimetry between whole brain radiotherapy (WBRT), hippocampal-sparing whole brain radiotherapy (HS-WBRT) and different VMAT-based focal radiotherapy approaches. Methods and materials: We identified 20 patients with one to ten brain metastases and at least one lesion larger than 15 cm 3 who had received WBRT as part of routine care. For each patient, we designed and evaluated five radiotherapy treatment plans, including WBRT, HS-WBRT and three VMAT dosing models. A dose of 20 Gy in 5 fractions was prescribed to the whole brain or target volumes depending on the plan, with higher doses to smaller lesions and dose-escalated inner planning target volumes (DE-iPTV) in VMAT plans, respectively. Treatment plans were evaluated using the efficiency index, mean dose and D0.1 cc to the target volumes and organs at risk. Results: Compared with WBRT, VMAT plans achieved a significantly more efficient dose distribution in brain lesions, especially with our DE-iPTV model, while minimising the dose to the normal brain and other organs at risks (OARs) ( p < 0.05). Conclusions: VMAT plans obtained higher doses to brain metastases and minimised doses to OARs. Dose-escalated VMAT for larger lesions allows higher radiotherapy doses to be delivered to larger lesions while maintaining safe doses to OARs.